Targeting MSME Opportunities through Brands: Strengthening the Legal Protection through Community Services - Fibrianti, Nurul; Suprapti, Duhita Driyah; Ardiansari, Anindya; Isnani, Isnani; Paramita, Niken Diah; Windiahsari, Windiahsari (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2022)
This paper explores the critical intersection of branding and legal protection for Micro, Small, and Medium Enterprises (MSMEs), acknowledging the pervasive misunderstanding among business actors regarding brands as intellectual property. Despite brands serving as integral identities for products, many MSME owners overlook their legal protection by the state. This gap in understanding exposes brands, including owned trademarks, to unauthorized use, posing significant risks to brand owners. Consequently, MSME actors often perceive brands merely as complementary additions to their products, neglecting their pivotal role in securing business viability. Recognizing the imperative for assistance in trademark registration to safeguard businesses, this paper advocates for proactive measures to educate and support MSMEs in navigating legal frameworks. By empowering MSMEs with the knowledge and tools for effective brand management and legal safeguards, this initiative aims to unlock opportunities for growth and competitiveness in the market landscape. Moreover, leveraging the potential of branding within tourism-rich regions like Karanganyar Regency, particularly the Matesih sub-district, offers a promising avenue for MSMEs to broaden product visibility. The influx of tourists presents an opportunity for MSMEs to position their products as souvenirs, thereby indirectly promoting their brands through consumer engagement. By capitalizing on protected brands, MSMEs can effectively tap into consumer-driven promotion and expand their market reach. This paper underscores the crucial role of community services in strengthening the legal protection of MSMEs' brands, thereby facilitating their sustained growth and resilience in the marketplace. Through strategic interventions and collaborative efforts, MSMEs can harness the power of branding